A feasibility study for waste paper briquettes: A green to approach to sustainable waste energy - Amican, Joyce Ann P., Arcilla, Jonel S., Ceballos, Ernest James, Gonzales, Shaina Kim E., Llacuna, Kyle Voughn K., Mangilit, Kayla E.. 4 0 16; 5 (2024)
Abstract This feasibility study investigates the potential of establishing a business that produces eco-friendly briquettes from recycled wastepaper in Tondo, Manila. The initiative addresses two critical challenges: meeting the demand for sustainable energy and managing waste effectively in the Philippines. The proposed Wastepaper Briquettes business utilizes abundant local waste paper to create a renewable energy alternative to traditional fuels such as charcoal, gas, and wood, thereby promoting environmental sustainability while reducing deforestation and landfill waste. This project aligns with global environmental goals by promoting a circular economy and reducing carbon emissions. The initiative demonstrates potential to serve as a model for sustainable enterprise while meeting energy needs effectively. The paper is aimed at investors, policymakers, environmental advocates, and local business owners. It outlines the feasibility of producing eco-friendly briquettes from recycled paper, highlighting sustainability, market potential, economic benefits, and financial viability to attract stakeholders and promote renewable energy solutions. It evaluates technical, financial, marketing, and socio- economic aspects to ensure the project's overall feasibility. By leveraging surplus paper waste, the proposed venture offers a sustainable alternative to traditional fuels, aiming to reduce deforestation and lower carbon emissions. With the rising demand for affordable, environmentally friendly energy solutions, this project offers significant economic and social benefits, including job creation, cost savings, and community development.
Feasibility Study: (BSBA major in Marketing Management) - Pamantasan ng Lungsod ng Maynila, 2024.
Keywords: 2 -- 0; 6; 20; 20; 2